Intercultural Learning Experiences for Sustainable Development from Engineering Schools - Miralles-Garcia, Josep Lluís; Liberado, Eduardo Verri [UNESP]; Gielen, Eric (Springer Nature, 2025)
This chapter focuses on several issues related to training in university engineering education. This process implies teamwork, multidisciplinarity, globality and multiculturalism and, consequently, the ability to express oneself clearly and reflect in an open public practice. This chapter focuses, first of all, on analyzing the training received by engineering students and the deficits that they present in the acquisition of transversal competences associated with achieving sustainability objectives in projects and plans that must necessarily have a multidisciplinary nature of teamwork. Secondly, the result of the global learning experiences carried out is analyzed based on the opinion expressed by the students who have participated in them, specifically undergraduate and master’s degree in engineering, São Paulo State University (Brazil), and master’s degree in civil engineering, Universitat Politècnica de València (Spain), through a multicultural and multidisciplinary collaborative experience. These students participated in some academic courses in COIL experiences with other universities. Finally, a reflection is made on how global learning experiences could be improved by modifying or incorporating activities in the study programs, with the aim that students obtain transversal competences related to international multidisciplinary teamwork for environmental decision making in the process of elaboration and execution of projects and plans related to engineering.
Keywords: Role playing simulations; STEM in virtual exchanges